Oral corticosteroids in acute urticaria. Issue 1 (20th January 2004) - Poon, M; Reid, C
Abstract : A short cut review was carried out to establish whether the addition of oral corticosteroids to antihistamines leads to a more rapid resolution of urticaria. Thirty nine papers were found using the reported search, of which two presented the best evidence to answer the clinical question. The author, date and country of publication, patient group studied, study type, relevant outcomes, results and study weaknesses of these best papers are tabulated. A clinical bottom line is stated.